Stress effects on ovine behaviour, physiology and the gastrointestinal microbiota - Kyriazopoulou, Panoraia (The University of Edinburgh, 2021)
Studies across different species have demonstrated the presence of an interplay between the brain, the gut and the microbiome, most commonly referred to as the gut-brain axis. Furthermore, it has been well documented that stress can affect neuroendocrinological and immunological systems, resulting in altered behaviours, as well as physiological dysregulations. In the past few decades, the effects of stress on the microbiome and the implications of the microbial community structure for the host have been the focus of many studies, aiming to shed light on this intricate and multi-pathway relationship. Despite this, most studies have been conducted on humans and rodents, with very few on farm animals, particularly ruminants. In ruminants, as in monogastrics, the gut accommodates high microbial concentrations and facilitates host-microbial interactions. What differentiates ruminants is the presence of the rumen, which hosts an equally important microbial community. This organ acts as a primary location for fermentation of feed and plays a pivotal role in animal metabolism, immunity and overall homeostasis. The effects of stress susceptibility, and more specifically psychological or behavioural stress, have been poorly explored in ruminants, despite their well-recognised and important effects on other aspects of animal health and welfare. This project therefore aimed to explore: 1) the effect of genetic predisposition to stress; 2) the long-term effect of prenatal and early life stressful events; and 3) effects of repeated and unpredictable management stress on the ovine gastrointestinal microbiome in conjunction with various physiology and behavioural aspects. The first experiment investigated genetic differences in gut and rumen microbial community structure and blood cortisol concentrations in 58 adult Romane ewes, previously selected on the basis of divergent reactivity to stress (30 ewes with high reactivity; 28 ewes with low reactivity). The two groups differed in their behavioural reactivity towards a temporary separation from congeners based on bouts of high bleats. Despite extensive analyses of the microbiota at the phylum, order and genus level, there were only small significant differences in the rumen and faecal microbiota, even when including cortisol levels in the analyses. For example, higher levels of cortisol were positively correlated with Ruminococcus abundance in faecal samples and Lactobacillus in the rumen, while Rikenellaceae abundance was positively correlated with reactive EBV scores in faecal samples. The second experiment investigated long-term effects of three prenatal stress treatments (Control, Negative and Alternative) and the effect of two early-life treatments (Isolation or Ewe Recognition tests) on the rumen microbial community structure of 35 8-month-old Scottish Mule lambs, at a stage when the rumen microbiome had assumed a relative stable and mature form. Sex and diet effects were confounded, while Prenatal Treatment did not appear to have an effect. Neonatal Treatment had an effect on relative abundances at the phylum level. The abundance of several bacterial species was correlated with higher or lower cortisol levels, such as Lactobacillus in Isolated females and Proteobacteria in Isolated males; these significant negative correlations suggested long-lasting effects of early life events. Finally, in the third experiment, we explored the effect of a 6-week mild unpredictable Chronic Stress paradigm on various behavioural (i.e., time budgets, reactions to a suddenness test) and physiology aspects (i.e. hormonal levels, heart rate and VFAs), as well as the rumen and gut microbiota structure. Forty-eight female Romane lambs were separated into two treatments: Non-Treated (NT, n = 24) and Mild Chronically Stressed Animals (MCS, n = 24). Amongst the most interesting results, indicating a treatment effect, were differences in synchronisation of animals resting and sleeping, duration of resting time, and reactions to novelty, as expressed by latency to approach the ball and contact time with the ball in the suddenness test. Microbiota diversity indices, particularly for the non-treated group, indicated a different development of the microbial community. In MCS animals, cortisol and serotonin levels indicated that several bacteria proliferate in the presence/absence of these hormones, but correlation scores were generally non-significant. In conclusion, it appears that the microbiota community structure in the rumen is not significantly affected by management stress or stress susceptibility, although the communication pathways between rumen bacteria and host behaviour warrant further exploration.
Keywords: stress; ovine; sheep; rumen; gastrointestinal; microbiome; 16S rRNA; mild stress; chronic stress